Effect of yerba mate extract on the performance of starch films obtained by extrusion and compression molding as active and smart packaging - Ceballos, Rocío Lais (2020)
Native or hydrolyzed starch and yerba mate extract (10 wt.% or 20 wt.%) films prepared by extrusion and compression molding were investigated. Native starch material (TPNS) exhibited lower water vapor permeability and higher Young's Modulus (E) compared to hydrolyzed starch matrix (TPHS) but decreases in strain at break (εb) and toughness (T). The incorporation of 10 wt.% of extract in TPNS led to greater E and εb and it resulted the most hydrophobic material. Conversely, TPHS with 20 wt.% of additive resulted the film with the highest εb and T, indicating a plasticizing effect of the extract in this concentration and system. All materials disintegrated after 10 weeks of burial, contributing to waste reduction. Biofilms containing yerba mate extract showed antioxidant activity and color changes in different pH, indicating their promising role as active and smart packaging for food, in accordance with the new trends for biodegradable and functional packaging.